Pengembangan Media IPA Berbasis Video Pembelajaran Interaktif Kearifan Lokal Kalimantan Selatan - Fitria Wulandari; Ria Mayasari; Yudha Adrian (Elementa: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
Interactive learning videos can be used as intermediaries that are quite effective in conveying learning. This is based on the fact that almost all students have smartphones that can be used to access the internet to study anytime and anywhere. The advantage of this interactive learning video is that users can operate on their respective smartphones and laptops with the Apk format. Using the Camtasia application when editing and the Smart Apps Creator application as an intermediary for the application creation process. This study aims to determine the validity and practicality of science learning media based on interactive video learning of local wisdom in South Kalimantan. This study uses research and development (R&D) methods with the development model used by the ADDIE (1990) development model. : 1) Analysis, 2) Design, 3) Development, 4) Implementation, 5) Evaluation. The subjects in the study were expert validators and users. The subject used in this research is the interactive science media of local wisdom of South Kalimantan. The trial was conducted face-to-face (offline). The data analysis technique used is quantitative from validation sheets, questionnaires, and qualitative from comments and suggestions from research subjects. The results of this study indicate that the validity of the interactive science media of South Kalimantan local wisdom is declared valid. The results obtained from media experts from 3 experts include, material experts get the percentage results of 78% quite valid category, media expert assessment percentage 97% very valid category and linguist assessment percentage 81% very valid category. The results of the teacher's response to the practicality of the media get an average percentage assessment of 98% in the very practical category.